Preserving the Effectiveness of UNCLOS despite a Party’s Non-Appearance? Some Remarks on the Arctic Sunrise Arbitration (Netherlands V. Russia) in the Context of Human Rights Protection - Balcerzak, Michał (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
On August 14th 2015 an Arbitral Tribunal established under Annex VII to the 1982 United Nations Convention on the Law of the Sea (UNCLOS) delivered an Award on the Merits in the matter of the Arctic Sunrise Arbitration (The Kingdom of the Netherlands v. the Russian Federation).The Arctic Sunrise case constitutes an interesting basis of discussion for several reasons, one of them being that it was the first case in which the respondent state refused to appear before a court or tribunal constituted under UNCLOS. The uniqueness of the Arctic Sunrise arbitration may also stem from the fact that it appears to be the first case in the UNCLOS-based dispute settlement scheme which concerned a vessel other than a fishing vessel or a war ship. But more importantly, the Arctic Sunrise case allowed the Arbitral Tribunal to examine the question of how and to what extent it may apply “other rules of international law” not incompatible with UNCLOS. Following a brief overview of the facts of the case, the analysis focuses on the ITLOS Order of November 22nd 2013 concerning provisional measures and the Arbitral Tribunal Order of August 15th 2015 on the merits of the case.
Keywords: UNCLOS; skuteczność; Arctic Sunrise Arbitraż; Prawa człowieka